Hydrogen sulfide alleviates 2,4-dichlorophenol toxicity and promotes its degradation in Phanerochaete chrysosporium - Chen, Anwei; Zeng, Guangming; Chen, Guiqiu; Zhang, Chang; Yan, Ming; Shang, Cui; Hu, Xinjiang; Lu, Lunhui; Chen, Ming; Guo, Zhi; Zuo, Yanan (Chemosphere (Oxford), 2014)
•H2S alleviated 2,4-DCP toxicity and improved its degradation by P. chrysosporium.•H2S shortened the time required for 2,4-DCP complete degradation.•H2S alleviated 2,4-DCP caused oxidative stress and improved cell viability. In this study, the H2S donor, sodium hydrosulfide (NaHS) was used to pretreat Phanerochaete chrysosporium in order to improve its ability to degrade 2,4-dichlorophenol (2,4-DCP). When pretreated with 100μM NaHS, P. chrysosporium was able to degrade 2,4-DCP completely in 24h, whereas the degradation efficiency of the untreated control was only 57%. The 2,4-DCP-induced oxidative stress was alleviated by NaHS, and the percentage of surviving cells increased by 32%. H2S or HS−, rather than other compounds derived from NaHS, were responsible for promoting 2,4-DCP degradation by P. chrysosporium. The results of this study suggest that H2S treatment is a potential strategy to alleviate environmental stress and improve the efficiency of the biological removal of pollutants from wastewater.